Medical records confidentiality and public health research: two values at stake? An italian survey focus on individual preferences - Virgilia Toccaceli; Corrado Fagnani; Maria Antonietta Stazi (SAGE Publishing, 2015)
In a time when Europe is preparing to introduce new regulations on privacy protection, we conducted a survey among 1700 twins enrolled in the Italian Twin Register about the access and use of their medical records for public health research without explicit informed consent. A great majority of respondents would refuse or are doubtful about the access and use of hospital discharge records or clinical data without their explicit consent. Young and female individuals represent the modal profile of these careful people. As information retrieved from medical records is crucial for progressing knowledge, it is important to promote a better understanding of the value of public health research activities among the general population. Furthermore, public opinions are relevant to policy making, and concerns and preferences about privacy and confidentiality in research can contribute to the design of procedures to exploit medical records effectively and customize the protection of individuals' medical data.